“BAKSO BOSS”: Evaluating the Impact of Serious Games Using GDLC and FFFL-HS for Small and Medium Enterprises (SMEs) - Ramdhan, Dimas; Bramanta Pandya Wisesa, Gede (Bina Nusantara University, 2025)
Small and Medium Enterprises (SMEs) are fundamental to economic growth, substantially aiding employment and income generation. Many SMEs face sustainability issues from deficient management and limited financial literacy, particularly in Indonesia (where they form 99% of businesses and 95% of employment). Financial literacy—making informed financial decisions —is crucial for owners to manage resources and improve outcomes effectively. This study addresses this critical gap by evaluating the impact of